2019
DOI: 10.1101/671719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of perineuronal nets in the adult cortex by the electrical activity of parvalbumin interneurons

Abstract: Perineuronal net (PNN) accumulation around parvalbumin-expressing (PV) inhibitory interneurons marks the closure of critical periods of high plasticity, whereas PNN removal reinstates juvenile plasticity in the adult cortex. Using targeted chemogenetic in vivo approaches in the adult mouse visual cortex, we found that transient electrical silencing of PV interneurons, directly or through inhibition of local excitatory neurons, induced PNN regression. Conversely, excitation of either neuron types did not reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…3c and Supplementary Fig. 5), as previously reported 40,41 . Of the 4 analyzed lecticans, Neurocan was the most abundant and was expressed by different neuronal cell types and astrocytes.…”
Section: Resultssupporting
confidence: 89%
“…3c and Supplementary Fig. 5), as previously reported 40,41 . Of the 4 analyzed lecticans, Neurocan was the most abundant and was expressed by different neuronal cell types and astrocytes.…”
Section: Resultssupporting
confidence: 89%
“…As mentioned previously, although PNN development has been strongly linked to neuronal activity 3,24,34 , PNN integrity and assembly are likely orchestrated by the complex integration by PV neurons of cues originating from multiple cell types 35,36 . Accordingly, we found that the expression of genes encoding for the major canonical components of PNNs were strongly enriched in oligodendrocyte-lineage cells, in particular in OPCs, while PV neurons barely expressed any of those components.…”
Section: Discussionmentioning
confidence: 94%
“…Because parvalbumin neurons have been shown to be particularly sensitive to stress and glucocorticoids, in particular early-life stress [27][28][29][30][31][32] , we can speculate that elevated glucocorticoids in CA victims 33 can impact PV+ neuron function earlyon. This could translate into increased GABA release following GR activation 31 , and indirect increase in the recruitment of PNNs, which has been directly linked to PV+ neuron activity 34,35 and GABA levels 36 . A myriad of factors could however indirectly affect PV+ cells during this period of protracted maturation associated with childhood and adolescence, such as increased pro-inflammatory cytokine expression associated with ELA 28,37 or changes in neurotrophic factor expression [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…PNNs are honeycomb-like structures that enwrap soma and proximal dendrites of (mostly) PV + neurons (review: Testa et al 2019). Recent reports indicate the activity level of PV + neurons cell-autonomously regulate the production of PNNs and PNN-modifying enzymes even in adulthood (Devienne et al 2019). In the Fmr1 −/y mouse, a delay of both PV + and PNN development is visible, which in this mouse is caused by an overproduction of the PNN modifier MMP-9 during the auditory critical period (Wen et al 2018).…”
Section: Discussionmentioning
confidence: 99%